Study of perinatal outcomes in normal and borderline oligamnios - Prasad, Divya R.; Nair, Neelima V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Oligamnios is a common cause of perinatal mortality and morbidity, but the outcome of borderline oligamnios, defined as Amniotic Fluid Index (AFI) between 5 and 8, is less clear. This study aims to find out the effect of borderline oligamnios on perinatal outcomes in pregnancies beyond 37 weeks. Methods: An observational prospective study of 131 antenatal mothers with AFI between 5 and 8, after 37 weeks of gestation was conducted in Sree Gokulam Medical College and Research Foundation from October 2017 to September 2019. These observations were compared with that of 131 antenatal mothers with normal AFI beyond 37 weeks of gestation. The observations according to fetal heart rate abnormalities, meconium staining of amniotic fluid, mode of delivery, low birth weight babies, APGAR score, the need of neonatal intensive care unit (NICU) admissions due to neonatal complications were statistically analysed. Results: Both groups were comparable with respect to age, parity and gestational age. In those with borderline oligamnios, fetal heart rate abnormality was seen in 21% (28), meconium stained amniotic fluid in 18% (23), 70% (91) delivered vaginally and 30% (40) underwent caesarean section, 31% (41) babies weighed below 2.5 kg and 21% (27) neonates needed NICU admissions. In those with normal AFI, none showed fetal heart rate abnormality, 2% (3) showed meconium staining, 93% (122) delivered vaginally and 7% (9) underwent caesarean section, 11% (14) babies weighed below 2.5 kg and 3% (4) neonates needed NICU admissions. Conclusions: Borderline oligamnios is associated with poor perinatal outcome. AFI can be used as an adjunct to other fetal surveillance methods. It helps to identify those infants at risk of poor perinatal outcome.